152k views
0 votes
Solve the equation 5(x-3) = 11 -3 (x-2)

User OneWinged
by
5.8k points

1 Answer

4 votes

Answer:

x = 4

Explanation:

5 multiplied by x and 5 multiplied by -3

5x - 15 = 11 -3(x - 2)

-3 multiplied by x and -3 multiplied by -2

5x - 15 = 11 - 3x + 6

Add 15 to both sides

5x = 26 - 3x + 6

Add 3x to both sides

8x = 26 + 6

Add 26 + 6

8x = 32

Divide 32 by 8

x = 4

User Chris Yo
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.